Analysis of English Phonological Performance between Sindhi Male and Female Learners - Joyo, Muhammad Ashraf; Memon, Rafique Ahmed (Pakistan Languages and Humanities Review, 2023)
This paper presents acoustic analysis of twenty English vowels and diphthongs i.e. /ʌ/, /ɑ: /, /æ/, /e/, /ə/, /3:/, /I /, /i: /, /ɒ/, /ɔ:/, /ʊ/, /aʊ/, /əʊ/, /u:/, /aɪ/, /eɪ/, /ɔɪ/, /eə/, /ɪə/ and /ʊə / produced by Second Language learner Sindhi speakers. This paper analysis acoustic realization of Sindhi speaking undergraduates between male and female. It investigates as to how much acoustic difference is between male and female speakers regarding formant one (F1) and formant two (F2). The study uses the parameters of vowel quality formant one and formant two (F1 & F2). The information was gathered via collecting voice samples from 30 subjects (fifteen male and fifteen female) from University of Sindh campus Nasuhahro Feroze, Sindh. The study focuses the height and the quality of vowels and diphthongs to determine the acoustic difference between them. The study finds that the F1 and F2 values of female participants are higher than the male participants. The hypothesis was that the production of the vowels and diphthongs of male and female differ from each other.